2007
DOI: 10.1093/ajcn/85.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dairy calcium or supplementary calcium intake on postprandial fat metabolism, appetite, and subsequent energy intake

Abstract: Increased calcium intakes from dairy products attenuate postprandial lipidemia, most probably because of reduced fat absorption, whereas supplementary calcium carbonate does not exert such an effect. This may be due to differences in the chemical form of calcium or to cofactors in dairy products. Calcium did not affect appetite sensation, glucose metabolism, or gut hormone secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
134
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(147 citation statements)
references
References 42 publications
4
134
3
6
Order By: Relevance
“…The 175 ml tap water ingested together with the test compounds contained 21 mg calcium, primarily as CaCO 3 . Although high doses of calcium seem to have an anti-obesity effect (Zemel, 2002), the present dose seems too small to have an effect on thermogenesis, substrate oxidation or food intake (Lorenzen et al, 2007).…”
Section: Respiratory Measurementsmentioning
confidence: 65%
“…The 175 ml tap water ingested together with the test compounds contained 21 mg calcium, primarily as CaCO 3 . Although high doses of calcium seem to have an anti-obesity effect (Zemel, 2002), the present dose seems too small to have an effect on thermogenesis, substrate oxidation or food intake (Lorenzen et al, 2007).…”
Section: Respiratory Measurementsmentioning
confidence: 65%
“…More recently, however, Boon et al only observed a tendency towards an increased faecal fat excretion on high-Ca (1200 or 2500 v. 400 mg) diets (23) . In support of a decreased fat absorption, Lorenzen et al (24) SFA are known to increase total and LDL-cholesterol, most probably by suppressing LDL-receptor activity (25) . The reduced absorption of SFA may, at least in part, contribute to the LDL-cholesterol-lowering effects of Ca.…”
Section: Effects Of Calcium On the Serum Lipid Profilementioning
confidence: 99%
“…A number of mechanisms have been proposed explaining observed low bioavailability of carotenoids from fermented maize. Due to disruption of matrix possibly by activated endogenous enzymes and microorganism, there is an increase in concentration of calcium which might enhance saponification of free fatty acids leading to reduced fat absorption and increase in fatty acid excretion in feces (Lorenzen et al., 2007). Fatty acids are very critical during absorption of lipophilic carotenoids.…”
Section: Effect Of Fermentation On Nutrients and Mineralsmentioning
confidence: 99%